Characterization of VspB of Borrelia turicatae, a Major Outer Membrane Protein Expressed in Blood and Tissues of Mice - Pennington, Pamela M. (American Society for Microbiology, 1999)
Serotypes A and B of the relapsing fever spirochete Borrelia turicatae produce different disease manifestations in infected mice. Whereas serotype B causes more severe arthritis and reaches higher densities in the blood of mice than serotype A, serotype A invades the central nervous system earlier than serotype B during infection. These differences between serotypes A and B in mice are associated with the expression of different surface proteins, VspA and VspB, respectively, in the culture medium. To determine whether these proteins, in particular, VspB, are also expressed in vivo, scid mice infected with B. turicatae were studied. The expression of VspB by spirochetes in the blood was demonstrated in Coomassie blue-stained polyacrylamide gels and Western blots with a specific monoclonal antibody. Indirect immunofluorescence and immunoperoxidase studies confirmed the expression of VspB in the blood and also demonstrated VspB expression in the joints and heart. The gene for VspB was next identified and cloned by using partial amino acid sequencing, reverse transcriptase PCR, and a specific monoclonal antibody. The vspB gene encodes a protein of 216 amino acids that is 68% identical to VspA of B. turicatae and 44 to 56% identical to representative Vsp and OspC lipoproteins of other Borrelia spp. The processed VspB protein was distinguished from 26 other Vsp and OspC proteins by a high predicted isoelectric point at 9.39. The promoter region for vspB was similar to the promoter region for the vsp33 gene of Borrelia hermsii and for the ospC gene of Borrelia burgdorferi, two genes known to be environmentally regulated. These studies established that the virulence-associated VspB protein is expressed by spirochetes in the mouse and that VspB is a novel member of the Vsp-OspC family of proteins.